TV Digital Transition in Italy and the Impact on Pupils' Academic Performance - Andrea Caria; Daniele Checchi; Dimitri Paolini (Institute of Labor Economics (IZA), 2025)
This paper studies the impact of television on student achievement in Italy, utilizing the staggered rollout of digital television across Italian provinces to isolate television's influence. Using data from national educational assessments (INVALSI) collected in four grades from 2009 to 2012, we uncover a negative effect of television on school performance by applying difference-in-differences techniques. We observe a positive correlation between TV viewing and test scores for a subset of the survey. Still, the negative impact is partly confirmed when instrumenting hours of view with the availability of digital channels. We also find significant heterogeneity: foreign-born pupils benefit from the greater availability of TV channels, while children with graduate parents experience less significant achievement losses.
Keywords: 2; I24; O33; 330; digital television switchover; school performance